Eco-friendly behaviour study: Factors affecting reusable shopping bag purchases among Malaysian Gen Z - Hiew, Ming Hui; Kan, Kelly Sin Kit (2024)
In recent years, the widespread use of plastic bags has become a detrimental effect to our mother earth, particularly due to its non-biodegradable nature, which lead to pollution in both terrestrial and marine ecosystems. The existence of RSBs serves as a more sustainable alternative to people, as it was designed for repeated use and often made from durable materials. In Malaysia, Generation Z, which constitutes the largest population group, is increasingly aware of environmental issues and more likely to prioritize the well-being of the planet over individual convenience. This generation is becoming a driving force behind the shift towards more sustainable consumption practices. Hence, this study has investigated the PI of RSBs among Generation Z in Malaysia. Stimulus-Response (SR) model and attached 5 key variables will be the backbone of our study to examine the purchase intention of reusable shopping bags which encompass, green awareness (GA), green attitude (GATT), green responsibility (GR), green knowledge (GK) and green trust (GT). By sending out the questionnaire, data of 384 Malaysian Generation Z respondents was gathered. The collected data had deployed into SPSS to check the relationship between these variables. The findings indicate that 3 out of 5 hypotheses have a significant relationship which influence the PI of RSBs. The remain hypotheses do not have positive relationship with the PI of RSBs. This research can provide valuable insights for both researchers and practitioners, helping them better understand on factors that influence Malaysian Generation Z and enabling them to take appropriate actions to increase the intention to purchase RSBs